Pengaruh Pengarah Aliran Pada Intake Manifold Sepeda Motor Terhadap Emisi Gas Buang - Perpustakaan UGM, i-lib ([Yogyakarta] : Laboratorium aekologi Fak. Biologi UGM, 2006)
This research aims to study the influence of turbulator on intake manifold motocycle to exhaust gas emission. In this research, three types of turbulators were made with various type 2, 3 and 4 blades installed in front and rear side of intake manifold, to get 9 combinations of turbulator pair. The test was subyected to Suzuki Shogun R 110 FD motocycle, with the variation at 1500, 2000, 2500, 3000, 3500, 4000 and 4500 rpm. Exhaust gas emission were measured using infrared Gas analyzer (Protech Flux 5000 srl-firenzeItaly). The result shows that the turbulator can increase the turbulence of stream inside the intake manifold, the fuel and air mixture is more homogen and the combustion in the combusting chamber runs better. All of these, in turn, could decrease the level of CO and increase the CO2 and HC level in the emitted gas. Turbulator with the best performance is the one using double blades. Keywords: turbulator, intake manifold motocycle, exhaust gas emission